Pelatihan Pengelolaan Keuangan Keluarga dalam Rangka Meningkatkan Literasi Keuangan di Desa Kasturi - Syarifudin, Syahrul; Nurfatimah, Siti Nuke; Wiharno, Herma (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2023)
This article is the result of community service activities that the author did in Kasturi Village, Kuningan Regency. This community service program was carried out with the theme